5α‐reductase inhibitors: Evaluation of their potential confounding effect on GC‐C‐IRMS doping analysis. Issue 11 (11th August 2021) - Iannella, Loredana; Colamonici, Cristiana; Curcio, Davide; Botrè, Francesco; de la Torre, Xavier
Abstract: 5α‐reductase inhibitors (5‐ARIs) are considered by the World Anti‐doping Agency as potential confounding factors in evaluating the athlete steroid profile, since they may interfere with the urinary excretion of several diagnostic compounds. We herein investigated 5α‐reductase inhibitors from a different perspective, by verifying their influence on the carbon isotopic composition of 5α‐ and 5β‐reduced testosterone and nandrolone metabolites. The GC‐C‐IRMS analysis was performed on a set of urine samples collected from three male Caucasian volunteers after the acute and chronic administration of finasteride in combination with the intake of 19‐norandrostenedione, a nandrolone precursor. The excretion and the isotopic profile of androsterone (A), etiocholanolone (Etio) 5α‐androstane‐3α, 17β‐diol (5αAdiol), and 5β‐androstane‐3α, 17β‐diol (5βAdiol) were determined as well as those of 19‐norandrosterone (19‐NA) and 19‐noretiocholanolone (19‐NE). Pregnanediol (PD) and pregnanetriol (PT) were also measured as endogenous reference compounds to define the individual endogenous isotopic profile. Our results confirmed the impact of finasteride, especially if chronically administered, on the enzymatic pathway of testosterone and nandrolone, and pointed out the influence of 5‐ARIs on δ 13 C values of the selected target compounds determined in the IRMS confirmation analysis. Abstract : 5α‐reductases inhibitors are listed in the WADA TD2021EAAS document as confounding factors influencing the athlete's urinary steroid profile, since they interfere with the metabolic pathway of the androgenic steroids. Their effect on the individual isotopic composition of testosterone and 19‐norsteroids 5α‐ and 5β‐reduced metabolites commonly detected in doping control analyses was here investigated. A comprehensive analysis was performed after acute or chronic administration of finasteride through the methods already validated in our laboratory.